A SYSTEMATIC REVIEW: UNDERSTANDING ENVIRONMENTAL DRIVING FACTORS OF HERITAGE BUILDING DEGRADATION - Fishol Hamdi, Nur Fisya; Salleh , Nurul Hamiruddin (Journal of Surveying, Construction and Property, 2025)
As the realm responds to nature's will, environmental factors are often cited as threatening the heritage building's wholeness and genuine character. Evolution in this research field has discussed various fractions of elements into these factors. Inevitably, this Systematic Literature Review (SLR) aims to comprehensively understand the extent and nature of environment, such as humidity, temperature fluctuations, pollution, and biological growth, that influence heritage buildings' degradation. Focusing on scholarly articles between 2020 and 2024 from reputable databased of Scopus and ScienceDirect, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework and systematic review of the filtered articles, the study found the contributed insights of the key area. The findings are categorized around three main themes: (1) Environmental and Climatic Impacts, (2) Material-Specific Degradation Mechanisms in Heritage Buildings, and (3) Diagnostic and Preventive Technologies for Heritage Building Preservation. The review reveals that moisture and temperature as the main environmental factors causing material decay, show up the cracking, erosion, and biological growth. Air pollution hastens chemical degradation, whereas natural disasters cause immediate and widespread loss in structural integrity. This paper calls underlining interdisciplinary collaboration to respond to environmental challenges ensuring the structural integrity of heritage buildings for future generations.